Status of treatment adherence related to anxiety and management of type 2 diabetes outpatients treatment at Military Hospital 105, 2021 (Vietnam Journal of Community Medicine, 2022)
A cross-sectional descriptive study was conducted on 270 patients with type 2 diabetes undergoing outpatient treatment at Hospital 105, in which the rate of reaching the treatment goal was very low: 31.5% and 71.7% had with hypertension. Objectives: (1) describe the rate of adherence to treatment and (2) analyze some factors related to treatment adherence. The results showed that the percentage of patients who adhered to the drug regimen was 81.5%, the follow-up regimen was 48.2%, the compliance rate to the physical activity regimen was 61.1%, and the compliance regimen was followed. nutrition is 32.2%, adherence to home blood sugar control regimen is 14.1%. The proportion of patients with anxiety is 26.7%. There was a statistically significant relationship between counseling activities of medical staff and the rate of medication adherence and follow-up (p
Keywords: Diabetes, treatment adherence; anxiety, factors related to treatment adherence.